Home Transcutaneous Electrical Stimulation Therapy to Treat Children With Anorectal Retention: A Pilot Study - Yik, Y.I.; Stathopoulos, L.; Hutson, J.M.; Southwell, B.R. (Blackwell Publishing, 2016)
Aim: As transcutaneous electrical stimulation (TES) increased defecation in children and adults with Slow-Transit Constipation (STC), we performed a pilot study to test if TES can improve symptoms (defecation and soiling) in children with chronic constipation without STC and transit delay in the anorectum. Methods: Children with treatment-resistant constipation presenting to a tertiary hospital had gastrointestinal nuclear transit study (NTS) showing normal proximal colonic transit and anorectal holdup of tracer. TES was administered at home (1 hour/day for 3 months) using a battery-powered interferential stimulator, with four adhesive electrodes (4 × 4 cm) connected so currents cross within the lower abdomen at the level of S2–S4. Stimulation was added to existing laxatives. Daily continence diary, and quality-of-life questionnaires (PedsQL4.0) were compared before and after TES. Results: Ten children (4 females: 5–10 years, mean 8 years) had holdup in the anorectum by NTS. Nine had <3 bowel motions (BM)/week. After three months TES, defecation frequency increased in 9/10 (mean 0.9–4.1 BM/week, p = 0.004), with 6/9 improved to ≥3 BM/week. Soiling reduced in 9/10 from 5.9 to 1.9 days/week with soiling, p = 0.004. Ten were on laxatives, and nine reduced/stopped laxative use. Quality-of-life improved to within the normal range. Conclusion: TES improved symptoms of constipation in >50% of children with treatment-resistant constipation with isolated holdup in the anorectum. Further studies (RCTs) are warranted in these children.